2012
DOI: 10.1111/sum.12006
|View full text |Cite
|
Sign up to set email alerts
|

Response of Italian ryegrass (Lolium multiflorum Lam.) to coffee waste application on a humid tropical sandy soil

Abstract: A greenhouse experiment was conducted to study the effect of coffee waste (CW) application on growth and mineral nutrition of Italian ryegrass in a tropical Arenosol. Dry CW was applied at three rates (5, 10, 20 t/ha) and thoroughly mixed with topsoil (0-25 cm), placed in pots and seeded with Italian ryegrass (Lolium multiflorum Lam.) according to a completely randomized design with six replicates. The application of CW greatly stimulated uptake of Ca, Mg, K, N and P, resulting in a significantly increased dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
14
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 21 publications
9
14
1
Order By: Relevance
“…Therefore the application of coffee husk compost might be contributed not only by supplying nutrients (including N, P, K and micronutrients) through mineralization but also by making P available to the plant as a result of its liming effect. This finding agrees with Kasongo et al (2013) and Nduka et al (2015) who reported the liming effect of coffee husk amendments on tropical acid soils.…”
Section: Plant Height and Stem Diametersupporting
confidence: 93%
See 3 more Smart Citations
“…Therefore the application of coffee husk compost might be contributed not only by supplying nutrients (including N, P, K and micronutrients) through mineralization but also by making P available to the plant as a result of its liming effect. This finding agrees with Kasongo et al (2013) and Nduka et al (2015) who reported the liming effect of coffee husk amendments on tropical acid soils.…”
Section: Plant Height and Stem Diametersupporting
confidence: 93%
“…Similarly, application of coffee husk compost without lime increased coffee seedling leaf dry matter weight by 108.3-266.7%, over the control with increasing rate (Figure 1). The result was in line with Kasongo et al (2013) who reported the application of coffee husk increased dry matter of rye grass on tropical acid soil. The highest leaf dry matter weight( 0.44 g) was obtained from plots received the highest coffee husk compost rate without lime (18.75 g/pot) and followed by combined application of lime (4 g/pot) and coffee husk compost (12.5 g/pot) which gave 0.43 g leaf dry matter weight.…”
Section: Leaf Dry Mattersupporting
confidence: 92%
See 2 more Smart Citations
“…According to Solomon (2006), high quality compost can be prepared from a mixture of 70% coffee pulp/husk, 20% FYM and 10% top soil or 70% coffee pulp,10%FYM,10% leguminous plant materials and 10% top soil. Some literatures (Taye et al, 2003;Solomon et al, 2008;Kasongo et al, 2011;Dzung et al, 2013;Kasongo et al, 2013;Nduka et al, 2015) have indicated that coffee waste is a valuable organic amendment, particularly for highly weathered soils of the humid tropics. Kasongo et al (2011) demonstrated the efficiency of coffee waste in improving the physico-chemical quality of Arenosols under humid tropical conditions.…”
Section: Coffee Husk and Pulp Compostmentioning
confidence: 99%